GENERAL ATTITUDES TOWARDS AND READINESS FOR MEDICAL ARTIFICIAL INTELLIGENCE AMONG STUDENTS AT NAZARBAYEV UNIVERSITY SCHOOL OF MEDICINE. - Sembekova, Anara (Nazarbayev University School of Medicine, 2023)
Introduction: Artificial intelligence is taking over the leading positions in medical technologies. AI in healthcare not only performs basic computational tasks, but also exceeds human performance in many areas of healthcare. Aim: This study aims to analyze the attitudes and readiness of students at Nazarbayev University School of Medicine (NUSOM) to the upcoming AI integration. Methods: 91 students were asked to fill out an online survey that collected data of respondents’ characteristics and AI familiarity, general attitudes, and general readiness assessment scales. The General Attitudes towards Artificial Intelligence Scale (GAAIS) developed by Schepman and Rodway (2020) and the Medical Artificial Intelligence Readiness Scale for Medical Students (MAIRS-MS; Karaca et al., 2021) were used in the study. Results: Most of the students had a low knowledge of AI with a mean = 45.56. Majority of the participants did not have any educational experience both in (95.6%) and outside (85.7%) the institution. Positive attitudes section: mean = 2.75 (SD = 0.64), while negative attitudes: mean = 3.01 (SD = 0.81). The readiness mean = 2.42 (SD = 0.60) out of 5.00. Conclusion: The research determined that most of the students had negative to neutral attitudes and poor readiness to medical AI. However, knowledge about AI and positive attitudes had a significant correlation with preparedness. The findings can be used to inform educational policymakers and educational institutions to develop curriculums involving AI, and ensure its ethical and optimized application in medicine. Keywords: artificial intelligence, machine learning, healthcare, medicine, attitudes, readiness, medical students
Keywords: Type of access: Restricted; Medical Students; Education; Artificial Intelligence